PENGARUH STRATEGI PEMASARAN TAHU TERHADAP MINAT BELI KONSUMEN PADA SUPER TAHU 20 DI DESA TERUSAN KECAMATAN BATURAJA TIMUR KABUPATEN OGAN KOMERING ULU - Hema Malini; Safaruddin; M. Arif Gunawan (Pojok Publisher, 2024)
This research aims to determine the influence of marketing strategies on consumer buying interest. In this research, descriptive research methods are used, namely research methods using descriptive research methods, namely research that seeks to explain solutions to current problems based on data. From the data analysis obtained by the results of a simple linear regression test, the equation is obtained, namely Y= 1.268 + 0.952X. Based on the R value of the correlation coefficient obtained using the interpretation guideline table, it can be seen that R = 0.931 is in the position 0.800 - 1.000, so it is stated below that it is very strong, while the r square figure (coefficient of determination) is 0.867 or 86.7%. This value shows that the contribution of all independent variables, namely Marketing Strategy (X), is 86.7% of the dependent variable, namely Purchase Interest (Y), and can be said to be quite strong.